Educação e sustentabilidae :Assentamento Maria da Paz - João Câmara/RN - Paula, Hiramisis Paiva de (2005)
This work is a research and action in the field of enviromental education, oriented for the construction of the land s distribuction of the Maria da Paz Settling, in João Câmara/RN, as process of social learning, collecive production of new knowledge, values and attitudes related to the environment. It was consolidated through a partnership beteween the UFRN (GERAH/DARQ and GEPEM/DEPED), MST and INCRA/RN. The drawing that represents the way the space organization of the settling was made constructed through effort of many people, in a process of dicussion with the community had as technical support the environment inventory (soil, vegetation, water resources, and others) allowing the agro-ecology zoning of the settlers participation conditions, their contradiction and conflicts, the challenges that appear in the search for consensus and the factor that creat chages